Reaching the south: metal-catalyzed transformation of the aromatic para-position. Issue 84 (25th August 2016) - Dey, Aniruddha; Maity, Soham; Maiti, Debabrata
Abstract : This article highlights the various protocols developed till date for selective installation of suitable functional groups at the para -position of arenes. Abstract : Regioselective functionalization of aromatic arenes has created a rapid insurgence in the modern era of organic chemistry. While the last few years have witnessed significant developments on site-selective ortho - and meta -C–H transformations, there existed very few reports on para -C–H functionalization. Recent advancements on template assisted protocols in para -C–H activation has emerged as a popular and convenient feat in this area. This review highlights the various protocols developed over the years for selective installation of suitable functional groups at the para -position of arenes thereby transforming them into value-added organic cores.